Linking pollen quality and performance of Neoseiulus californicus (Acari: Phytoseiidae) in two‐spotted spider mite management programmes. Issue 2 (27th May 2016) - Khanamani, Mostafa; Fathipour, Yaghoub; Talebi, Ali Asghar; Mehrabadi, Mohammad
Abstract: BACKGROUND: It has been shown that pollen as a dietary supplement may increase the establishment of generalist predatory mites, and therefore pest control by these mites can be provided. Life table studies were performed to evaluate the nutritional value of seven different pollens (almond, castor‐bean, date‐palm, maize, bitter‐orange, sunflower and mixed bee pollen) as a supplementary food source for the spider mite predator Neoseiulus californicus McGregor. In addition, the nutritional quality of each pollen species was assessed through morphological and chemical analysis. RESULTS: Preadult duration was longer when the predator fed on castor‐bean pollen (10.01 days) and bee pollen (9.94 days) compared with the others (5.58–7.27 days). The cohort reared on almond pollen had the highest intrinsic rate of increase ( r ) (0.231 day −1 ), and those on mixed bee pollen had the lowest r (0.005 day −1 ). The levels of nutritional content (sugar, lipid and protein) were significantly different among tested pollens. CONCLUSIONS: Comparison of N. californicus life table parameters on different diets revealed that the almond pollen (and after that the maize pollen) was a more suitable diet than the others. These findings will be useful in developing appropriate strategies for conservation of N. californicus to control spider mites. © 2016 Society of Chemical Industry